YAP-driven malignant reprogramming of oral epithelial stem cells at single cell resolution - Farhoud Faraji; Sydney I. Ramirez; Lauren M. Clubb; Kuniaki Sato; Valeria Burghi; Thomas S. Hoang; Adam Officer; Paola Y. Anguiano Quiroz; William M. G. Galloway; Zbigniew Mikulski; Kate Medetgul-Ernar; Pauline Marangoni; et al. (Nature Communications)
Abstract Tumor initiation represents the first step in tumorigenesis during which normal progenitor cells undergo cell fate transition to cancer. Capturing this process as it occurs in vivo, however, remains elusive. Here we employ spatiotemporally controlled oncogene activation and tumor suppressor inhibition together with multiomics to unveil the processes underlying oral epithelial progenitor cell reprogramming into tumor initiating cells at single cell resolution. Tumor initiating cells displayed a distinct stem-like state, defined by aberrant proliferative, hypoxic, squamous differentiation, and partial epithelial to mesenchymal invasive gene programs. YAP-mediated tumor initiating cell programs included activation of oncogenic transcriptional networks and mTOR signaling, and recruitment of myeloid cells to the invasive front contributing to tumor infiltration. Tumor initiating cell transcriptional programs are conserved in human head and neck cancer and associated with poor patient survival. These findings illuminate processes underlying cancer initiation at single cell resolution, and identify candidate targets for early cancer detection and prevention.